Primary angiitis of the central nervous system: response to mycophenolate mofetil. Issue 10 (17th September 2009) - Chenevier, F; Renoux, C; Marignier, R; Durand-Dubief, F; Hermier, M; Streichenberger, N; Vukusic, S; Confavreux, C
Abstract : Primary angiitis of the central nervous system (PACNS) is a rare inflammatory disease restricted to the CNS of unknown cause. Clinical presentation and evolution are highly variable with potentially fluctuating signs and symptoms. Brain imaging often shows supratentorial ischaemic lesions. Definite diagnosis is established by brain biopsy. Treatment usually combines glucocorticosteroids and cyclophosphamide. A case of PACNS is reported here, which was proved by a brain biopsy and characterised by unusually prominent involvement of the posterior cerebral fossa. Successful treatment with mycophenolate mofetil in combination with steroids is described.